Mechanical properties and biocompatibility of co-axially electrospun polyvinyl alcohol/maghemite - Ngadiman, N. H. A. (SAGE Publications Ltd, 2016)
Electrospinning is a simple and efficient process in producing nanofibers. To fabricate nanofibers made of a blend of two constituent materials, co-axial electrospinning method is an option. In this method, the constituent materials contained in separate barrels are simultaneously injected using two syringe nozzles arranged co-axially and the materials mix during the spraying process forming core and shell of the nanofibers. In this study, co-axial electrospinning method is used to fabricate nanofibers made of polyvinyl alcohol and maghemite (γ-Fe2O3). The concentration of polyvinyl alcohol and amount of maghemite nanoparticle loading were varied, at 5 and 10 w/v% and at 1-10 v/v%, respectively. The mechanical properties (strength and Young's modulus), porosity, and biocompatibility properties (contact angle and cell viability) of the electrospun mats were evaluated, with the same mats fabricated by regular single-nozzle electrospinning method as the control. The co-axial electrospinning method is able to fabricate the expected polyvinyl alcohol/maghemite nanofiber mats. It was noticed that the polyvinyl alcohol/maghemite electrospun mats have lower mechanical properties (i.e. strength and stiffness) and porosity, more hydrophilicity (i.e. lower contact angle), and similar cell viability compared to the mats fabricated by single-nozzle electrospinning method.